Severe ethylene glycol poisoning of 56 years old woman – case report - Klatka, Barbara Zofia; Terpiłowski, Michał Jerzy; Janeczko, Dominika Anna; Orzeł, Anna Katarzyna; Hołowczuk, Magdalena; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Backgrounds: Ethylene glycol poisoning is one of the heaviest poisonings in the toxicological practice of. Ethylene glycol is quickly absorbed from the digestive tract. Its toxicity is the result of combining few different mechanisms. Metabolites of decomposition, especially glycolic acid, are responsible for appearance of metabolic acidosis. Precipitated crystals of calcium oxalate additionally impair the function of organs such as kidneys, central nervous system (CNS) and circulatory system. Worldwide, from 2013 to 2018 about 30% of ethylene glycol poisoning cases end in death. Case report: We present the case of 56 years old woman, who was admitted to Toxicology Department because of ethylene glycol poisoning. We could observe presence of metabolic acidosis, respiratory insufficiency and organ damage. The patient has been treated pharmacologically and has been given specific antidote. Due to the ethylene glycol intoxication, metabolic acidosis and increasing parameters of kidney failure the patient also underwent hemodialysis. Conclusions: In pathogenesis of ethylene glycol poisoning toxic metabolits are crucial. The diagnosis of ethylene glycol is often a very hard task. In the clinical aspect it is based on the interview, a set of syndromes and biochemical tests and targeted toxicological tests. This kind of poisoning occur the most often among patients addicted to alcohol. It may lead to multi- organ damage or even death. It is very important to react quickly and implement pharmacotherapy and hemodialysis. The other essential aspect is to improve the level of knowledge of students and doctors about symptoms, diagnostics and proper proceeding with a patient poisoned with ethylene glycol. According to statistics and knowing how often the alcohol poisoning happens it is necessary to have knowledge in this field, be fluent in management and choosing methods of treatment in such cases.